2009
DOI: 10.1073/pnas.0907303106
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that chytrids dominate fungal communities in high-elevation soils

Abstract: Periglacial soils are one of the least studied ecosystems on Earth, yet they are widespread and are increasing in area due to retreat of glaciers worldwide. Soils in these environments are cold and during the brief summer are exposed to high levels of UV radiation and dramatic fluctuations in moisture and temperature. Recent research suggests that these environments harbor immense microbial diversity. Here we use sequencing of environmental DNA, culturing of isolates, and analysis of environmental variables to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
111
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(121 citation statements)
references
References 42 publications
7
111
3
Order By: Relevance
“…), and along the continental divide in Colorado. Out of these environmental sequencing surveys significant numbers of Naganishia species were only found at the highest sites sampled in Colorado (Freeman et al 2009). Importantly, these sites were also the only sampled sites (among the global sites listed above) that had soil pH values (pH 4.5) similar to those found on the three volcanoes (Table 1).…”
Section: Landscape Patterns Of Naganishia Distributionmentioning
confidence: 99%
“…), and along the continental divide in Colorado. Out of these environmental sequencing surveys significant numbers of Naganishia species were only found at the highest sites sampled in Colorado (Freeman et al 2009). Importantly, these sites were also the only sampled sites (among the global sites listed above) that had soil pH values (pH 4.5) similar to those found on the three volcanoes (Table 1).…”
Section: Landscape Patterns Of Naganishia Distributionmentioning
confidence: 99%
“…The program MOTHUR v. 1.8.0 [23] was used to calculate the genetic distance matrices, and the Mantel tests were performed in R (http://pbil.univ-lyon1.fr/ade4html/mantel.rtest.html). Microbial biomass levels were measured using the chloroform fumigation method and other soil parameters were measured using standard methods as described elsewhere [5,14,15,24]. Algal and cyanobacterial counts were done using epifluorescence microscopy as described elsewhere [25].…”
Section: Methodsmentioning
confidence: 99%
“…Our preliminary work in the Himalayas and similar sites in other high mountain ranges with prominent subnival zones [5,14,15] indicated that these sites had many environmental and ecological attributes similar to those of the Dry Valleys of Antarctica. Yet there have been no comparative studies of these ecologically similar but geographically distant systems.…”
Section: Introductionmentioning
confidence: 99%
“…Our calculations show that soil primary production inputs of approximately 10 800 kg C yr −1 (calculated using the production rate of 240 kg C ha −1 yr −1 from Freeman et al (2009b) over 20 % of the watershed) are indeed higher than atmospheric inputs, as suggested by Freeman et al (2009b). For barren soils, respiration C losses were calculated at approximately 12 600 kg C yr −1 , using an average 2002 summer season respiration rate of 56 kg C ha −1 yr −1 (0.013 g C m −2 h −1 ; Freeman et al, 2009a), estimated to also occur for 90 d and over 20 % of the watershed area. According to Caine (1995, and references therein), roughly 20 % of the catchment also comprises lowlying vegetation.…”
Section: Relevance Of Atmospheric Wet and Dry Deposition Inputs For Tmentioning
confidence: 99%
“…Alpine heterotrophic bacteria such as Polaromonas, found at Niwot Ridge and other barren alpine environments, can oxidize even recalcitrant carbon sources (Darcy et al, 2011 and references therein). At Niwot Ridge, chytrids have been found to dominate the fungal biodiversity (Freeman et al, 2009a) and are known to be partially supported by aeolian inputs, such as pollen. Therefore, the importance of atmospheric organic C inputs for these and other alpine organisms is a key question for future research.…”
Section: Chemical Quality Of Oc In Atmospheric Depositionmentioning
confidence: 99%